2011
DOI: 10.2147/ijn.s21755
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of osteoblasts to a nanorough titanium implant surface

Abstract: This work considers the adhesion of cells to a nanorough titanium implant surface with sharp edges. The basic assumption was that the attraction between the negatively charged titanium surface and a negatively charged osteoblast is mediated by charged proteins with a distinctive quadrupolar internal charge distribution. Similarly, cation-mediated attraction between fibronectin molecules and the titanium surface is expected to be more efficient for a high surface charge density, resulting in facilitated integri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 68 publications
1
39
0
Order By: Relevance
“…However, Gongadze et al demonstrated that titanium implants with low values of the surface potential promote osteoblast adhesion and the formation of the new bone [66]. The extensive review of Guo et al [38] demonstrates that the bone cell adhesion on a biomaterial and the initial stage of bone proliferation are quite sensible to the surface charge and its polarity.…”
Section: Discussionmentioning
confidence: 99%
“…However, Gongadze et al demonstrated that titanium implants with low values of the surface potential promote osteoblast adhesion and the formation of the new bone [66]. The extensive review of Guo et al [38] demonstrates that the bone cell adhesion on a biomaterial and the initial stage of bone proliferation are quite sensible to the surface charge and its polarity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that osteoblasts proliferate better on surfaces stiffer than most polymers 84 as well as that mesenchymal stem cells (MSCs) differentiate into neurons on soft surfaces and osteoblasts on the stiff ones 85 , which explains how come the dispersion of CAP particles throughout a polymeric matrix leads to an increased Young’s modulus and increased bioactivity of the composite material at the same time 86 . Moreover, it is a rule of thumb that biomaterials in general should be rough so as to promote cell attachment 87,88 , except in a few cases, including joint and some soft tissue implants for which smooth surfaces are more desirable; impregnation of polymers with inorganic nanoparticles contributes to this surface roughness and makes additional processing steps such as etching or sandblasting unnecessary. Precipitation of HAp throughout an acellular dermal matrix at low supersaturation, the process which is also known as biomimetic mineralization of scaffolds, has correspondingly yielded a markedly more viable surface for the proliferation of periodontal ligament stem cells 89 .…”
Section: Polymeric/cap Compositesmentioning
confidence: 99%
“…15 Irrespective of the location of an implant (a blood-contacting, orthopaedic or dental implant) the first step made after the implantation is the adsorption of proteins from the surrounding tissue or medium. Gongadze et al [16][17][18] proposed a mechanism for the adhesion of the cells to a nanorough titanium implant surface with sharp edges, exhibiting more surface area and electric charge than a micro-sized surface. These surface characteristics of a contact surface affect the functional activity of cells.…”
Section: Introductionmentioning
confidence: 99%